ANALISIS PENGAWASAN DAN KEWENANGAN PEMERINTAH DALAM PENERBITAN SERTA PENCABUTAN IZIN USAHA PERTAMBANGAN (IUP) NIKEL DI RAJA AMPAT DITINJAU DARI PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Ridha Nababan; Sintia Harianti; Otista Sembiring; Santi Sinurat; Salwa Khairani Tarigan; Kevin Tambunan; Taufiq Ramadhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the legal regulations for the issuance and revocation of nickel Mining Business Permits (IUP) in Raja Ampat, assess whether the revocation of Mining Business Permits (IUP) by the Ministry of Energy and Mineral Resources (ESDM) is in accordance with the principles of legality and the General Principles of Good Governance (AUPB), and examine its efforts to protect the right to a good and healthy environment. This study uses a normative juridical method with a regulatory approach and a conceptual approach in State Administrative Law. The results show that the issuance and revocation of Mining Business Permits (IUP) have a clear legal basis in the Mineral and Coal Law and other related regulations, including regulations on the environment and government administration. After the amendment to the Mining Law, the authority to issue and revoke Mining Business Permits (IUP) rests with the central government through the Ministry of Energy and Mineral Resources (ESDM). However, in its implementation, these administrative actions must still comply with the principles of legality and the General Principles of Good Governance (AUPB), such as legal certainty, accuracy, transparency, and the public interest. Revocation of a Mining Business Permit (IUP) can be considered legally valid if carried out by an authorized official, through proper procedures, and based on violations of applicable provisions, particularly those related to environmental protection. This action also has a significant impact on protecting the community's right to a good and healthy environment, particularly in the Raja Ampat region, which has high ecological value. Therefore, the use of government authority must be carried out carefully, transparently, and responsibly to achieve a balance between development and environmental protection.